Impact of Bio-accelerated Farming against Conventional Farming System on Green Gram (Vigna radiata L.) under Rainfed Condition: Adaptive Management Enhances the Resilience to Climate Change - Dahal, Dipen; Ghosh, J.; Chhetri, Binoy (International Journal of Bio-resource and Stress Management, 2019)
The field experiments was conducted at the Instructional Farm of Uttar Banga Krishi Viswavidyalaya, Pundibari, Coochbehar, West Bengal, India during 2011-2012. The objective was to assess the effect of chemical free bio-accelerated and conventional farming system on growth, yield attributes, yield, nutrients uptake, quality and microbial population of green gram. The farm is situated at 26o 19’86”N latitude and 89o23’53”E longitude at an elevation of 43.0 m above mean sea level. Results revealed that the growths, yield attributes, quality and microbial population of green gram were recorded higher in chemical free bio-accelerated compared to the conventional farming system. From the pooled data the highest yield was recorded under bio-accelerated farming (1500 kg ha-1) compared to the conventional farming system (1375 kg ha-1). The highest moisture percentage recorded under conventional farming (65.37%) than bio-accelerated farming system (63.35%). The nitrogen (50.40 and 73.88 kg ha-1), phosphorus (10.53 and 11.32 kg ha-1) and potassium (67.68 and 123.60 kg ha-1) uptake by crop was recorded highest under the conventional farming compared to bio-accelerated farming system. The application jiwanmrita recorded significantly higher number of microbial population in the soil of bio-accelerated farming than the conventional farming system.From the pooled data analysis showed 62.50 microbes in bio-accelerated and 39.75 microbes in conventional farming before sowing which increased up to 97.25 microbes and decreased to 31.94 microbes in bio-accelerated and Conventional farming system. Among the chemical free bio-accelerated farming system pest incidence was found to be lower as compared to the conventional farming system.